Haitian voodoo dolls revealed by X-ray: From radiology to medical anthropology. Issue 4 (December 2015) - Augias, Anaïs; Benmoussa, Nadia; Jacqueline, Sophie; Jaeger, Julie Nogel; Muller, Anne-Laure; Charlier, Philippe
Abstract: Objectives: The aim of our study was to carry out the radiographic examination of seven dolls recently collected in the central cemetery of Port-au-Prince (Haiti). These dolls and evidence obtained can be used as a psychological tool to aid in victimological forensic analysis. This can improve our knowledge of magical-religious rituals of Haitian voodoo. Materials and methods: Radiological examination was performed on these ethnographic objects through X-Ray using a flat panel detector Primax Clisis©. Furthermore, an additional observation was performed using a microscope (Leica EZ4 HD©). All X-ray images have been read on plain film and on a diagnostic workstation by both a medical anthropologist and a radiologist. Results: These studies bring to light many objects inserted into the voodoo dolls, such as needles, zippers or buttons, while direct observation by microscope confirmed the insertion of human hairs. Linking such discoveries with the current data of traditional Haitian voodoo allowed us to better understand the use, purpose, and fabrication process of these dolls. Discussion: Medical imaging is essential for the understanding and interpretation of these rituals, and brings knowledge to medical anthropology, especially since there is not much data on this sorcery practice, which is prohibited and punishable by the Haitian law. Conclusion: The use of forensic tools, such as radiography, on Haitian voodoo artifacts is unprecedented, as is the introduction of this kind of ethnographic objects in the forensic field of victimology. Highlights: We present here the original radiological examination of voodoo dolls recently collected in the cemetery of Port-au-Prince (Haiti). Dolls were examined by radiography using a flat panel detector Primax Clisis©. Organic remains analysis was carried out using binocular lenses (Leica EZ4 HD©). Such a non-invasive technique permits the virtual autopsy of artifacts, and a better knowledge of magical-religious practices of Haitian voodoo.